Vulneración de derechos constitucionales en la Ley de Comunicación en el ejercicio de la actividad informativa al obligar a los comunicadores privados a prestar un servicio público - Vargas Morocho, Jorge Tobías (2014)
The Communications Law, has been immersed in some controversies and discussions by legal analysts, journalists, communicators and the general public before approval and more then this because several articles that violate important constitutional rights is the obligation imposed on them to private communicators to provide a public service, this is set to a number of articles of the law but the main problem consists in Article 71 of the law states that when .... "Information is constitutional right and a public good ; and social communication to be done through the media is a public service that should be provided with accountability and quality ... "I believe that this normalization distorts the exercise of information activity , when they are forced to private communicators provide a public service when the reality from the informative work that started in the world and society by private communicators is to serve the public, which is very different from providing a public service that is necessary to clarify and differentiate from this statement in the law there are a number of items that require private communicators to provide free services to the State comprehensive control over its work of journalists who are actually completely violating the rights of this group of civil society , as is the right to private property, free association , to work, to free enterprise , freedom of expression and communication to name and information as required by the constitution. The problem associated with this type of standards lies not only in the aforementioned law if not in the way of establishing a public service, as the first item should clarify that the Constitution of the Republic of Ecuador there is no article establishing communication and information as a public service , public services understood as institutions created by the Constitution and the Act clearly provide a public service to the public , non-profit and the service is fully funded by the Ecuadorian state, so this public service not on par with the Constitution if not inconsistent causing a number of inconsistencies between these two standards and of course huge violation of rights not only to private communicators if not the entire citizenry . Therefore it is evident that a legal reform to repair this legal error is necessary. In view of the controversy and raised from the adoption of the Communications Law by actors involving thematic analysis have seen fit to do a field study , documentary, analytical and legal of course what is required by the Act communication to establish communication and information as a public service and violating the rights of private communicators to impose certain obligations from this unconstitutional , so I put this work in knowledge from conceptual , doctrinal contributions and major legal ; bearing in mind the great contribution of fieldwork obtained from the use of surveys and interviews, which centrally involves the problem. Legal research was developed with the use of hierarchically Ecuadorian law from the Constitution of the Republic of Ecuador , Human Rights, Communications Law , Regulations of the Communications Law Communication Law and different countries which could narrow research successfully , and as mentioned the different literature sources that explain concepts, definitions of key words of research as the historical background and evolution of communication and information in general to the particular is so throughout the process research development and efficient work in the analysis and justification of the problem , both in terms of the literature review and even more on the analysis of the results of the field research shows. They are body of this research work, an accomplished detail of the different materials, methods, procedures and techniques used to obtain and sustainable papers valid data. In conclusion after all investigative work I can say that a legal reform Communications Law is necessary to prevent the violation of constitutional rights of private communicators who are being forced to provide a public service through his journalism .